2016
DOI: 10.1111/ijmr.12123
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Entrepreneurial Autonomy in Franchised Outlets: A Systematic Review of the Empirical Evidence

Abstract: Entrepreneurial autonomy among franchisees is a persistent management challenge.There is a lack of empirical synthesis of its drivers, its consequences, and how it can be integrated with the standardization requirements in franchise systems. Various theoretical and empirical studies have stressed that merging franchisee autonomy with the franchisor's desire for uniformity is extremely difficult. This paper aims to provide a systematic review of the relevant empirical studies in order to identify a range of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 104 publications
(307 reference statements)
1
83
1
Order By: Relevance
“…We have organized this review of empirical research on technological diversification around the antecedents and outcomes of technological diversification as well as associated moderating effects (Figure ). This structure is based on established formats which we adapted in line with our research objectives (Figure ) and the research patterns observed in the focal literature (Dada ; Hitt et al . ; Hoskisson and Hitt ; Hutzschenreuter and Israel ; Kotlar et al .…”
Section: Empirical Research On Technological Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have organized this review of empirical research on technological diversification around the antecedents and outcomes of technological diversification as well as associated moderating effects (Figure ). This structure is based on established formats which we adapted in line with our research objectives (Figure ) and the research patterns observed in the focal literature (Dada ; Hitt et al . ; Hoskisson and Hitt ; Hutzschenreuter and Israel ; Kotlar et al .…”
Section: Empirical Research On Technological Diversificationmentioning
confidence: 99%
“…We have organized this review of empirical research on technological diversification around the antecedents and outcomes of technological diversification as well as associated moderating effects ( Figure 3). This structure is based on established formats which we adapted in line with our research objectives ( Figure 1) and the research patterns observed in the focal literature (Dada 2018;Hitt et al 2006;Hoskisson and Hitt 1990;Hutzschenreuter and Israel 2009;Kotlar et al 2018;Raisch and Birkinshaw 2008). Although research considers external, orga-nizational and group-level factors, the vast majority of work has focused on the organizational level, in particular the relationship between technological diversification and organizational-level outcomes.…”
Section: Empirical Research On Technological Diversificationmentioning
confidence: 99%
“…The last aspect of entrepreneurial orientation is autonomy, understood as the capacity to independently explore and exploit market opportunities. The autonomy may be analyzed in the context of the entire organization or at the individual level (Al Mamun, Kumar, Ibrahim, & Bin, 2017;Anderson, Covin & Slevin 2009;Dada, 2018). In the first case, it is equated with its independence in relation to specific stakeholders connected to networks of business relationships.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our prediction is that these will have the same impact on franchisors and franchisees in terms of serious conflict and early terminations generated within the system. The other set deals with the degree of entrepreneurial autonomy of franchisees; namely, the extent to which the franchisees are able to freely decide how to operate their outlets outside the standardized confines of the franchise system (Dada 2016). Autonomy provides franchisees with the freedom and flexibility they need for entrepreneurial activities (i.e., risk-taking, innovative, and proactive initiatives) (Lumpkin et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Autonomy provides franchisees with the freedom and flexibility they need for entrepreneurial activities (i.e., risk-taking, innovative, and proactive initiatives) (Lumpkin et al 2009). However, although the franchisor's autonomy is usually undisputed, that of franchisees is debatable (Grünhagen et al 2014;Dada 2016). We specifically examine franchisees' autonomy in two decision areas, pricing and local advertising.…”
Section: Introductionmentioning
confidence: 99%